Assertive Illocutionary Act Found in Rendall Park’s Speech Video at UCLA 2023 - I Gusti Bagus Niko Ari Putra; I Gusti Ayu Vina Widiadnya Putri (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2024)
In this study, the researcher focuses on the analysis of the Assertive Illocutionary Act Found in Rendall Park’s Speech video at The University of California, Los Angeles (UCLA) 2023. This study aims to find out the assertive illocutionary acts used in Rendall Park’s Speech Video at UCLA 2023 and the second is to find out the most dominant assertive illocutionary acts classification found in Rendall Park’s Speech at UCLA 2023 and analyze some of the utterances. This study made use of Searle's (1979) classification of illocutionary acts theory. The data collection for this study used the observation method. To analyze the data, a descriptive qualitative method is used in this study because the results presented from this research are in the form of using words. In this study, researchers managed to find five types of assertive illocutionary acts classification in the data source. The result of this research found there are 46 utterances indicating assertive illocutionary acts. There are 19 utterances as informing classification, 13 utterances as stating classification, 10 utterances as asserting classification, 4 utterances as boasting classification, and 1 utterance as complaining classification. Informing is the most dominant assertive classification that was founded in this speech.